2009
DOI: 10.1080/09585190903175647
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of gender discrimination in China – evidence from recruitment advertisements

Abstract: In this paper we present an analysis of recruitment advertisements that suggests that Chinese employers frequently discriminate on gender grounds, both directly and indirectly. We illustrate how employers continue to use entrenched stereotypes and perpetuate highly segregated expectations of men and women's roles at work, predominantly to the detriment of women and hindering their progress in the labour market. The paper concludes that while employers' recruitment practices are not the only cause of women's co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 16 publications
0
34
0
2
Order By: Relevance
“…Even amongst young Chinese urban professionals anticipating entry into the workforce, traditional gender roles appear pervasive; they expect women to perform more household tasks, be paid less and have less prestigious jobs (Coffey et al ., ). Further recent research indicates that employers frequently discriminate on gender grounds (Woodhams et al ., ). Chinese female employees are caught between contradictory expectations from their roles at home and at the workplace; they face a gap between high expectations inspired by the prevailing ideology and the reality of discrimination and inequality in the workplace as well as their typically assigned caring roles in the family.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Even amongst young Chinese urban professionals anticipating entry into the workforce, traditional gender roles appear pervasive; they expect women to perform more household tasks, be paid less and have less prestigious jobs (Coffey et al ., ). Further recent research indicates that employers frequently discriminate on gender grounds (Woodhams et al ., ). Chinese female employees are caught between contradictory expectations from their roles at home and at the workplace; they face a gap between high expectations inspired by the prevailing ideology and the reality of discrimination and inequality in the workplace as well as their typically assigned caring roles in the family.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…In China, the expectation that women should ‘serve’ appears to extend beyond the family sphere; it tends to be accepted as normal that women predominate in much service sector work. A recent study on recruitment advertisements in China reported that female applicants were sought for 71 per cent of jobs involving selling (Woodhams et al ., ). Therefore:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…Although the official rhetoric still evokes the figurative casting of women as holding up half the sky, research shows that female employees and managers experience widespread devaluation and discrimination (Bowen, Wu, Hwang, & Scherer, ; Granrose, ; Han, ; Maurer‐Fazio, Rawski, & Zhang, ). As Woodhams, Lupton, and Xian () found, traditional gender norms and expectations have a strong influence on recruitment and selection processes.…”
Section: Female Employment In the Chinese Contextmentioning
confidence: 98%
“…Third, the protection of women from discrimination has lessened further with the liberalization of the economy, where more women have become remote from the protection of the state as an employer (Cooke, ; Leung, ). Recent evidence suggests that employment discrimination is commonplace (Woodhams, Lupton, & Xian, ) and that women are more likely to be laid off and obliged to enter informal sectors of the economy where protection and support are lower still (Berik et al, ; Cook & Dong, ; Cooke, ).…”
Section: Women In the Chinese Economymentioning
confidence: 99%